Anatomical Variations of the Right Adrenal Vein: Concordance Between Multidetector Computed Tomography and Catheter Venography. Issue 3 (March 2017) - Omura, Kensuke; Ota, Hideki; Takahashi, Yuuki; Matsuura, Tomonori; Seiji, Kazumasa; Arai, Yoichi; Morimoto, Ryo; Satoh, Fumitoshi; Takase, Kei
Abstract : Adrenal venous sampling is the most reliable diagnostic procedure to determine surgical indications in primary aldosteronism. Because guidelines recommend multidetector computed tomography (CT) to evaluate the adrenal gland, some past reports used multidetector CT as a guide for adrenal venous sampling. However, the detailed anatomy of the right adrenal vein and its relationship with an accessory hepatic vein remains uncertain. The purpose of this study was to describe detailed anatomical variations of the right adrenal vein and to determine the concordance between CT and catheter venography in patients with primary aldosteronism. In total, 440 consecutive patients who underwent adrenal venous sampling were included. Four-phase dynamic CT was performed. Anatomical locations and variations of the right adrenal vein and its relationship with the accessory hepatic vein were compared with catheter venographic findings. Successful catheterization was achieved in 437 patients (99%). The right adrenal vein was visualized in the late arterial phase with CT in 420 patients (95%). The right adrenal vein formed a common trunk with the accessory hepatic vein in 87 patients (20%). CT identified the correct craniocaudal level of the orifice in 354 patients (84%). Anatomical variations, location, and angle of inflow of the right adrenal vein based on CT demonstrated high concordance with catheter venography. CT may provide useful information for preparation before adrenal venous sampling. Abstract : Supplemental Digital Content is available in the text.